Altering wettability to recover more oil from tight formations. (September 2016) - Brady, Patrick V.; Bryan, Charles R.; Thyne, Geoffrey; Li, Huina
Highlights: Experimental measurements show that solution pH, salinity, and hardness control adhesion of oil to the middle Bakken. Chemical controls over wettability alteration in tight formations are identified. A method for designing fracturing fluid and squeeze job overflush bulk chemistries to increase oil recovery is described. Abstract: We describe here a method for modifying the bulk composition (pH, salinity, hardness) of fracturing fluids and overflushes to modify wettability and increase oil recovery from tight formations. Oil wetting of tight formations is usually controlled by adhesion to illite, kerogen, or both; adhesion to carbonate minerals may also play a role when clays are minor. Oil-illite adhesion is sensitive to salinity, dissolved divalent cation content, and pH. We measure adhesion between middle Bakken formation oil and core to verify a surface complexation model of reservoir wettability. The agreement between the model and experiments suggests that wettability trends in tight formations can be quantitatively predicted and that the bulk compositions of fracturing fluid and overflush compositions might be individually tailored to increase oil recovery.